Plan and Simulation Yagi Micro-Strip Antenna for 10GHz Applications - Mohammed Khaire Hussain (NTU Journal of Engineering and Technology)
This paper shows a micro-strip antenna based on the yagi antenna principle, both singly and in a matrix. The suggested antenna can operate at a frequency of 10 GHz, which is in the X-band. The antenna specifications that were studied (Directivity, Gain, S11 Parameter, etc.). Two types of micro-strip Yagi antennas were simulated and compared; the first of which consisted of a single antenna and the second of which consisted of a matrix of two antennas. CST Microwave Studio Soft-ware 2019 was used for designing and simulation. The results were for antennas constructed for Gain (5.308dB) (9.682dB) and Directivity (6.016dB) (10.28), with the array antenna outperforming the first antenna by a wide margin.